The correlation and regression of hatching weight in relation to individual egg-weight in two broiler strains (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1973)
In the present investigation the influence of egg weight on hatching chick weight in two commercial broiler strain, wax studied. The hatching eggs coming from two different strains — Arbor Acres and Parks- GB, here named “A” and “B " respectively — were incubated during 21 days and 3 hours. No significant difference in chick weight was found between strains, although the Arbor Acres showed a slight tendency to be heavier than Parks-GB. A consistently and significantly positive linear relationship was found between hatching body weight and egg weight with “ r ” values of 0.791 and 0.786 for Arbor Acres and Parks-GB. Respectively. However, coefficient of determination (squaring of correlation coefficients) revealed that about 62.57% and 61.78% of the variation in chick weight could be accounted for- to the egg weight for Arbor Acres and Parks-GB strains, respectively. The regression equations obtained were as follows: Yi = 2,32 + 0,630 xi (Arbor Acres) e Yi = 0,1 + 0,661 xi (Parks-GB). According to these regressions, the increase of the chick weight averaged 0.630 g and 0.661 g fo r Arbor Acres and Parks-GB. respectively, when the egg weight was increased 1 gram.